The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques